Gratitude for Overseas Students: Kebersyukuran pada Mahasiswa Rantau - Dian Lestari; Effy Wardati Maryam (Academia Open, 2022)
This qualitative research study with a phenomenological approach aims to investigate gratitude among overseas students and identify the factors that influence their experience of gratitude. The study involved two participants who were overseas students at Muhammadiyah University of Sidoarjo. Semi-structured interviews were conducted to collect data, which was then analyzed using data collection, reduction, presentation, and drawing conclusions or verification. The findings revealed three aspects of gratitude: gratitude through the heart, gratitude through words, and gratitude through deeds. Several factors were identified as influencing gratitude in overseas students, including accepting destiny, knowledge, experience, social support, spirituality, establishing relationships, good intentions, religious practice, inner calmness, and positive thinking. The implications of this research contribute to a deeper understanding of gratitude among overseas students and provide insights for fostering a sense of gratitude in this population. Highlights: The study explores gratitude in overseas students and identifies factors influencing their experience. The research adopts a phenomenological approach to gain a deep understanding of the phenomenon. The qualitative research design utilizes semi-structured interviews for data collection and analysis. Keywords: Gratitude, Overseas students, Factors, Phenomenological approach, Qualitative research.